2015
DOI: 10.1155/2015/925631
|View full text |Cite
|
Sign up to set email alerts
|

Portulaca oleraceaL.: A Review of Phytochemistry and Pharmacological Effects

Abstract: Portulaca oleracea L., belonging to the Portulacaceae family, is commonly known as purslane in English and Ma-Chi-Xian in Chinese. It is a warm-climate, herbaceous succulent annual plant with a cosmopolitan distribution. It is eaten extensively as a potherb and added in soups and salads around the Mediterranean and tropical Asian countries and has been used as a folk medicine in many countries. Diverse compounds have been isolated from Portulaca oleracea, such as flavonoids, alkaloids, polysaccharides, fatty a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
197
0
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(253 citation statements)
references
References 51 publications
1
197
0
11
Order By: Relevance
“…The results of this study indicated that the antimicrobial component of the two herbs could be more soluble in ethanol as compared to water. Previous studies supported this result (Sun et al, 2012;Zhou et al, 2015). A recent study has shown that the flavonoid apigenin isolated from ethanolic extracts of Portulaca oleracea L. has antibacterial property and could be used to develop antibacterial drugs (Hanumantappa et al, 2014).…”
Section: Resultsmentioning
confidence: 73%
“…The results of this study indicated that the antimicrobial component of the two herbs could be more soluble in ethanol as compared to water. Previous studies supported this result (Sun et al, 2012;Zhou et al, 2015). A recent study has shown that the flavonoid apigenin isolated from ethanolic extracts of Portulaca oleracea L. has antibacterial property and could be used to develop antibacterial drugs (Hanumantappa et al, 2014).…”
Section: Resultsmentioning
confidence: 73%
“…The role of phagocytosis is primary the removal of microorganism and foreign bodies, but also the elimination of dead or injured cells. Phagocytic defects are associated with varied pathological condition in humans 21 .…”
Section: Resultsmentioning
confidence: 99%
“…As a promising green food and medicine, purslane is noted for its high contents of K, Ca and Mg, which play crucial roles in improving blood circulation and human immunity and reducing depression [2,4]. Table 3 shows that dietary mineral contents in both common purslanes were higher than that in conventional vegetables; in particular, the K content was the highest [6,20].…”
Section: Comparison Of Mineral Contentsmentioning
confidence: 99%
“…In addition, purslane has been reported to be the richest vegetable source of omega-3 (ω-3) fatty acids (FA) yet examined [3]. The abundance of high levels of these nutrients in purslane lead to its multiple effects as improving blood circulation and human immunity, prevention and treatment of cardiovascular disease and inhibition of microbial growth and so on [2,4]. Although purslane is still considered as a wild weed in most countries, it is now known as one of the most promising green foods, the most used medicinal plants and the "power food for the future" [5,6], and is eaten fresh, cooked, or dried and the interest of cultivating it as a food crop and herd-medicine has increased all over the world in recent years [5,7].…”
Section: Introductionmentioning
confidence: 99%